A method to calculate the bulk hardness of metal matrix composite using Hadfield steel reinforced with niobium carbide particles as an example. (September 2017) - Ma, Liang; Huang, Cheng; Dolman, Kevin; Tang, Xinhu; Yang, Jianjun; Shi, Zheng; Liu, Zhong-Sheng
Highlights: A conceptual model is proposed to calculate the bulk hardness of metal matrix composites. Hadfield steel reinforced with 15% vol niobium carbide particles is studied as an example. Hardness testing is simulated based on the calculated equivalent stress-strain curves. The effect of bonding between Hadfield steel and niobium carbide particles is investigated. Abstract: A conceptual model is proposed in this paper to calculate the bulk hardness of particle-reinforced metal matrix composites. Hadfield steel with niobium carbide particles is taken as an example to show the feasibility of this proposed method. A micro-scale concept called representative equivalent volume is used to investigate the heterogeneous microstructure and the impact of water quenching on the equivalent mechanical properties of the metal matrix composite. Furthermore, the continuum-scale indentation process used in laboratory hardness testing is simulated by the finite element method based on the stress-strain curves obtained from the micro-scale modeling. The simulated hardness is compared with laboratory measurements and a good agreement is observed confirming the model.